Differential T-cell responses in dogs with meningoencephalomyelitis of unknown origin compared to healthy controls - Barber, Renee; Barber, James (Frontiers in Veterinary Science, 2022)
Meningoencephalomyelitis of unknown origin (MUO) is a common disorder of dogs that results in mononuclear inflammation in the brain and / or spinal cord of dogs. MUO is presumed to be autoimmune but specific immunological aberrations have not been identified. This pilot study aimed to evaluate T cell production of two cytokines commonly implicated in autoimmune disease, interferon-gamma (IFNg) and interleukin-17 (IL17). Peripheral blood mononuclear cells were obtained from 12 dogs with MUO and 10 healthy controls, stimulated to activate intracellular signaling pathways, and stained with CD4, CD8, IFNg, and IL17 antibodies prior to analysis by flow cytometry. CD4+ and CD8+ T cells were evaluated and several significant differences were identified between MUO cases and healthy controls. First, overall and CD4+ IFNg-producing T cells were fewer in MUO cases. Second, although total numbers of IL17-producing lymphocytes were not different, there were more CD4+ IL17+ T cells in MUO cases than controls and fewer CD8+ IL17+ T cells in MUO cases than controls. These results support that immunological changes can be identified in peripheral blood cells of dogs with MUO and suggest that T helper type 17 (Th17) cells may play a role in pathogenesis.